Kajian Potensi Dan Peluang Serta Fasilitasi Pendaftaran HKI Untuk Produk Hasil Lomba Krenova Dan Hilirisasi Riset - Pratiwi Dwihapsari; Agus Tri Hananto (Badan Riset dan Inovasi Daerah Kota Surakarta, 2023)
Intellectual Property Rights (IPR) are an unavoidable necessity in an intellectually based economy. In contrast to the most classical economic approach which relies on natural resources, or the more modern economy which relies on the development of machinery and information technology, an intellectually based economy emphasizes exclusivity which originates from ideas and creativity. In the business world, IPR can be a very valuable asset for companies and individuals (Malkin, 2022). Companies that own IPR directly protect their creations and innovations, and can even maintain a strong market position. Apart from that, IPR can also help in building a strong brand and reputation for a product or company, which can be an important factor in winning business competition.